The Evolution of International Trade Agreements - Winham, Gilbert R. (Book collections on Project MUSE., 1992)
Today as economic boundaries are merging, dividing, and reforming, international trade plays a critical role in global stability. Winham offers an insightful analysis of how the current situation has developed and where it might lead.